Skill level, Cognitive Ability, Unemployment and Welfare - Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2004)
This paper examines the implications of that workers may not be able to estimate their true costs of acquiring skills. Consequently, too few workers may acquire skills. This allows for the possibility that subsidizing education is welfare improving. Furthermore, if the presence of skill-biased technological shocks increase unemployment, this may explain why the market it-self cannot respond to this by making it sufficiently attractive to acquire skills. Consequently, the trade-off in-between subsidizing education and thereby reducing unemployment and optimizing welfare may be eliminated. We analyse this issue in a simple educational model and next in a search equilibrium model including a skill choice decision.
hdl:10398/7593
Keywords: I20; J64; 330; Education; subsidies; efficiency; unemployment